2018
DOI: 10.1002/admi.201800897
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces of (Ultra)thin Polymer Films in Organic Electronics

Abstract: In this short review the energy level alignment of interfaces involving solution‐processed conjugated polymer (and soluble small molecules) films is described. Some general material properties of conjugated polymers and their solution‐processed films are introduced, and the basic physics involved in energy level alignment at their interfaces is then discussed. An overview of energy level bending in (ultra)thin conjugated polymer films (often referred to as “band bending”) is given and the effects of ion‐contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 104 publications
0
43
0
Order By: Relevance
“…We obtain a fitting line with two distinct slopes S = 0 and S = 1, which are corresponding to the two regions of F sub o E ICTÀ and E ICTÀ o F sub o E ICT+ respectively in the ideal ICT curve. 43,48,49 When F sub is smaller than 4.2 eV, the Fermi level is pinned to 2.8 eV. While when F sub is larger than 4.2 eV, F sub/org is equal to (F sub -1.4) eV.…”
Section: Resultsmentioning
confidence: 99%
“…We obtain a fitting line with two distinct slopes S = 0 and S = 1, which are corresponding to the two regions of F sub o E ICTÀ and E ICTÀ o F sub o E ICT+ respectively in the ideal ICT curve. 43,48,49 When F sub is smaller than 4.2 eV, the Fermi level is pinned to 2.8 eV. While when F sub is larger than 4.2 eV, F sub/org is equal to (F sub -1.4) eV.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that band bending in organic semiconductors beyond the first monolayer is primarily relevant for less ideal situations, e.g., for (intentionally or unintentionally) doped organic semiconductors [156,157] or when dealing with materials having defect-or disorder-induced states in the gap. [158] For example, Ishii et al [159] observed depletion-layer widths of ≈100 nm for C 60 /metal interfaces, while they found flat bands when using N,N′-bis(3-methylphenyl)-N,N′-diphenyl-[1,1′-biphenyl]-4,4′-diamine (TPD) as semiconductor. These flat bands they attributed to the high purity of the used TPD.…”
Section: Organic Monolayers Versus Multilayers and Doped Filmsmentioning
confidence: 99%
“…Therefore, in such situations instead of fractionally charging every molecule (FCT), a fraction of the molecules receives an integer charge, i.e., one observes integer charge transfer (ICT). [24,158] Depending on the intermolecular coupling, the charge might also be delocalized over a few molecules. [248] The FCT and ICT scenarios are schematically compared in Figure 12a, where in the case of FCT translational periodicity is preserved, while it is broken in the ICT case.…”
Section: The Integer Charge-transfer (Ict) Situationmentioning
confidence: 99%
“…The way S and R dev depend on the WF of the metal contacts pinpoints that the phenomenon responsible for these measured trends relates to the energetics of the metal-polymer interface. Interfacial dipoles are known to form at the conducting polymer-metal electrode interface, and depend on their WFs 15,[27][28][29][30][31] . The WF of PEDOT:Tos and PEDOT:PSS is typically 4.5± 0.2 eV eV and 5.0 ± 0.1 eV 32,33 , respectively.…”
Section: Resultsmentioning
confidence: 99%